2017
DOI: 10.1080/10803548.2017.1374583
|View full text |Cite
|
Sign up to set email alerts
|

Work environment investments: outcomes from three cases

Abstract: Work environment investments are important in order to create a healthy and safe workplace. This article presents findings from a seven-step interventions process aimed at examining and following-up work environment investments in small and medium-sized enterprises (SMEs), with a particular focus on air contaminants. Three different cases were analyzed and included in the study: (a) an educational center for welding; (b) a paint station in furniture manufacturing; (c) a joinery in furniture manufacturing. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
1
4
0
2
Order By: Relevance
“…Studies have found that work environment investment can be highly optimized in terms of OHS effects [2]. This study confirms these results, but also highlights the importance of focusing on the whole investment process, which, in this study, emerged in seven critical elements.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Studies have found that work environment investment can be highly optimized in terms of OHS effects [2]. This study confirms these results, but also highlights the importance of focusing on the whole investment process, which, in this study, emerged in seven critical elements.…”
Section: Discussionsupporting
confidence: 87%
“…The uniqueness of the present developed work environment investment model (critical elements) is the focus on the entire investment process for optimizing the effects, in terms of creating a safer work environment. As Rydell and Andersson [2] have shown, by following up three work environment investment cases, investments can be highly optimized through further decreasing hazards for workers. For optimizing the effects of the investments, Rydell and Andersson found that employee involvement, safety training, leadership engagement and follow-ups of the investment are important.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations